Pengembangan Learning Management System Dengan Model Project-Based Learning Untuk Pembelajaran Basis Data - Cintiya Cintiya; Martini Dwi Endah Susanti (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The learning process at SMKN 4 Bojonegoro faces challenges, namely the lack of digital infrastructure and learning that is still centered on teachers. Students and teachers have difficulty managing learning documents, both materials and assignments. Thus,  a learning management system with a project-based learning model  is needed that can be used in the learning process. This research aims to develop a learning management system with a project-based learning model  that can help students, teachers and admins in managing learning in the classroom. The learning management system is developed based on moodle with a project-based learning model. Moodle-based LMS is integrated with the code runner plugin.  Code runner plugins can help students practice coding without having to install additional software. The subject of this study is a software engineering student in class XI of SMK Negeri 4 Bojonegoro. This research uses the Research and Development (R&D)  method with the ADDIE (analyze, design, development, implementation, evaluation) model. Feasibility test  of  moodle-based learning management system with a project-based learning model  using blackbox testing and expert validation tests. The blackbox test on this LMS got valid results and the expert validation test got a very valid category.